ArtHist.net: internationales Fachforum der Kunstgeschichte (arthist e.V., 2001)
[Dt.:] ArtHist ist ein internationales und nicht-kommerzielles Forum der Kunstgeschichte im Verbund des H-Net (Humanities and Social Sciences Online). Es betreibt u.a. die Mailing-Liste H-ArtHist mit Beiträgen aus dem Bereich der Kunst-, Kultur- und Medienwissenschaften, darunter auch aktuelle Buchrezensionen. - [Engl.:] ArtHist is an inter-university, public, non-profit institution for publications and discussions concerning art history. The network is open for contributions on all artistic genres, media, and periods. Adhering to an open conception of "art", the list is not limited to the conventional interests and approaches of academic art history. In particular, it invites critical contributions on pictorial tradition as an aspect of a larger visual environment